1994
DOI: 10.1063/1.467467
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of vapor–liquid equilibria of linear quadrupolar fluids. Departures from the principle of corresponding states

Abstract: Improved vapor-liquid equilibria predictions for Lennard-Jones chains from the statistical associating fluid dimer theory: Comparison with Monte Carlo simulations Vapor-liquid equilibria of different quadrupolar linear Kihara fiuids have been studied, by using the Gibbs ensemble Monte Carlo technique. Coexistence curves for fiuids with elongations L * = LI u= 0.3, 0.6, and 0.8 and different quadrupoles are given. We analyze the effect of quadrupole moment on critical properties. Quadrupole moment increases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 46 publications
(2 reference statements)
1
42
1
Order By: Relevance
“…Easier choices 3,31 are possible, but in this case the parameters depend slightly on the particular thermodynamic states used to fit them. Moreover, we have found 19,20 that reduced critical temperatures are independent of elongation for the Kihara potential when a reduced dipole/quadrupole density is properly defined and we have made use of this fact here. The equations used in this work were Alternatively, eq 3 can be written as…”
Section: Simulation Conditions and Relation To Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Easier choices 3,31 are possible, but in this case the parameters depend slightly on the particular thermodynamic states used to fit them. Moreover, we have found 19,20 that reduced critical temperatures are independent of elongation for the Kihara potential when a reduced dipole/quadrupole density is properly defined and we have made use of this fact here. The equations used in this work were Alternatively, eq 3 can be written as…”
Section: Simulation Conditions and Relation To Experimentsmentioning
confidence: 99%
“…34 No systematic deviation was observed for the most complicated molecular shape or for the presence of internal rotation in the case of perfluorethane. We previously studied this case for carbon dioxide, with excellent results, 20 and we can predict that a model of carbon dioxide without quadrupole would have a critical temperature 60 K lower than the quadrupole model of actual CO 2. We have shown that this behavior is general when reduced quadrupole density is properly defined.…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact TIP4P provides a quadrupole moment and a ratio dipole/quadrupole in much better agreement with experiment. The effect of a quadrupole moment on the vapor-liquid equilibria of molecular models is well known [232,233,234]. However it seems that the role of the quadrupole on water properties has been overlooked in spite of some warnings about its importance [235,236,237,218,238,239].…”
Section: The Phase Diagram Of Watermentioning
confidence: 99%
“…Examples of applications of the method that have appeared in the past year include calculations of phase diagrams for diatomic Lennard-Jones molecules [31], dipolar and quadrupolar fluids [32,33], a realistic potential model for methanol [34] and methyl iodide [35]. Extensions of the technique to reactive and associating systems [36] as well as ionic systems [37] are available.…”
Section: The Gibbs Ensemble Methodsmentioning
confidence: 99%